ANALISIS TINGKAT EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) SEBELUM DAN SESUDAH DIALIHKAN MENJADI PAJAK DAERAH (Studi Kasus di Desa Watutumou, Kecamatan Kalawat, Kabupaten Minahasa Utara) - Christi, Kodoati N.; Runtu, Treesje; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2017)
Through the implementation of law No.28 of 2009 on local taxes and lavies, the tax collection authority of the land tax and rural and urban buildings (PBB-P2) is transferred to the local government. North Minahasa district government in this case Watutumou Village is one of the villages that have potentials in the local tax sector can maximize this policy as an effort to increase acceptance in realizing development in the region. This study aims toÂ determine the level of effectiveness of Land and Building Tax revenues before and after diverted into local taxes in Watutumou Village, the effort made by the village government to overcome the obstacles that arise in the process of acceptance of PBB-P2 and how the role of village government in optimizing the acceptance of PBB-P2. This study used descriptive quantitative method. The collection of data in this case is interview and documentation. The result of the research note that the effectiveness of PBB-P2 before and after deverted into the criteria effective. But in the year before and after diverted, the realization of PBB-P2 didnâ€™t reach the target specified due to certain obstacles, so it requires the effort and role of government in increasing the acceptance of PBB-P2. For the village government can further improve the acceptance of PBB-P2 with attention to human resource training, socialization and up to date data available in the village.Keywords : PBB-P2, effectiveness, village government